An archaeozoological and ethnographic investigation into animal utilisation practices of the Ndzundza Ndebele of the Steelpoort River Valley, South Africa, 1700 AD – 1900 AD - Ouzman, Sven (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2009.